Distribution Pattern and Corn Marketing Efficiency in South Lampung Regency - R Hanung Ismono; Restiana Restiana (Politeknik Negeri Lampung, 2011)
Background of the study is a corn’s production in Lampung province is high, but some companies of cattle feed is still lack of corn stock. This study aims to find out the distributíon patterns and marketing channels to analyze the efficiency of corn marketing in South Lampung regency. This study was conducted in Ketapang and Natar districts. Respondents of this study were 51 corn farmers, 11 traders and 3 consumers. Respondents were taken using Simple Random Sampling and Snowball Sampling method. This study uses distribution pattern analysis, marketing margins analysis and price elasticity transmissions analysis. Data collection was done by in-depth interviews and expressed both qualitatively and quantitatively . The study was conducted in September-November 2009. The results showed that 22, 48 percent of the corn in South Lampung distributed out Lampung and marketing of corn in South Lampung regency was still not efficient. Key words: distribution pattern , marketing efficiency, corn